Pendugaan Kehilangan Hasil pada Tanaman Padi Rebah Akibat Terpaan Angin Kencang dan Curah Hujan Tinggi - ,, Dulbari; Santosa, Edi; Koesmaryono, Yonny; Sulistyono, dan Eko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
AbstractRice lodging due to incident of extreme weather, i.e., combination of strong winds and high rainfall is eviden in Indonesia. However, yield loss in the area is rarely studied. In order to estimate yield loss on rice, a model for calculating the yield reduction was developed. The objective of present study was to analyze the effect of strong winds and high rainfall incidents on yield loss of rice in the field. The study was conducted at the Sawah Baru IPB, Bogor, Indonesia from February to April, 2016 on rice plots severe from natural incident of strong wind and high rainfall. The results showed that rice lodging from strong wind and high rainfall formed patterns and specific formations. We determined four major lodging formations, five lodging degrees, and eleven different patterns due to wind direction. Overall, lodging occured on research area of 27.6% with production loss up to 11.89%. This research showed that estimation of yield loss due to incident of extreme weather could be conducted in the level of field based on area of coverage and degree of lodging. Application of the model on wider area needs further evaluation. Keywords: Agronomic character, extreme weather adaptation, modelling, lodging, rice variety